The Apathy of students towards the study of Islamic studies in Nigerian Higher Institutions: (Tai Solarin University of Education (As a Case Study - Rahman, Lawal; H. S. A., Solarim (Al-Adab Journal, 2022)
This study investigates factors responsible for apathy or lack of interest in the study of Islamic Studies Education as a course in Tai Solarin University of Education, Ijagun,Ijebuode, Ogun State of Nigeria. It is believed generally that some students show lack of interest in some courses at the under graduate level and this eventually interferes with enrolment or population of students that study the course or affect their performance if they eventually enroll for the course. This study therefore investigates the factors responsible for the apathy of students towards Islamic studies and equally proffer solution to the identified problems. In carrying out this research the descriptive approach was used. The research instrument used are the Pearson correlation coefficient and simple percentages. A more positive correlation coefficient (closer to 1) reveal the validity and reliability of the instrumentThis study unfolds that Inferiority complex, parental influence and poor back ground in Islamic Studies are major factors responsible for the low enrolment of students in Islamic Education Department of Tai Solarin University of Education. It was therefore recommended that good remuneration of teachers, parental support, provision of Arabic remedial class and educating the masses on the relevance of Islamic studies will go a long way to increase the turnout of students who study Islamic Studies in the University.